Regulating Vertical Housing: Analysis of Indonesia’s Law No. 20/2011 in Kudus Urban Development - Syahputra, Mohammad Firdaus (Indonesian Journal of Agrarian Law, 2024)
The development of flats in Kudus City is a solution to land limitations along with the increasing need for housing. This article analyzes the implementation of Law No. 20 of 2011 concerning Flats in a local context, including national regulations, implementation in the field, and the challenges faced. The results of the analysis show that the implementation of regulations in Kudus is not optimal due to the absence of special regulations, licensing obstacles, lack of legal education, and weak supervision. Strengthening of regional regulations, harmonization of central-regional policies, and increasing the role of government in socialization and supervision are needed in order to realize sustainable vertical housing.